Combination of Rail Fence and Route Cipher: Dual Encryption Strategy in Digital Messages - Asih Lestari; Nanda Putri Tami; Fabianus Delan Saputra; Erni Widarti (Telkom University, 2025)
In today’s digital era, the protection of personal and sensitive information has become a critical challenge due to the rapid growth of cyber threats and unauthorized access. Encryption remains one of the most effective strategies to ensure confidentiality and integrity of digital communication. This study proposes a dual encryption approach by combining two classical transposition algorithms: Rail Fence Cipher and Route Cipher. The Rail Fence Cipher rearranges plaintext into a zig-zag pattern across multiple rails, producing an initial ciphertext that obscures the original structure. The Route Cipher then strengthens security by placing this ciphertext into a matrix and reading it according to a predefined route, such as spiral or zig-zag, thereby generating a second ciphertext with higher complexity. The combination of these methods creates layered encryption that is more resistant to cryptanalysis compared to using either algorithm alone. Experimental implementation using Python demonstrates that the dual encryption strategy produces ciphertext that is significantly more randomized and difficult to predict. While this approach does not guarantee absolute security against modern attacks, it offers a practical solution for small-scale applications, educational purposes, and scenarios requiring lightweight encryption. The findings encourage broader adoption of encryption techniques and highlight the relevance of classical algorithms in understanding fundamental cryptographic principles and developing adaptable security strategies in the evolving digital landscape.